Evaluation of the Implementation of Inventory using the EOQ Method at Toyota Spare Parts Store Period 2021 – 2023 - Marcheani Virginee, Fionyta; Rakhman , Abdullah (Ridwan Institute, 2024)
Economic order quantity (EOQ) is one of the inventory management methods used to optimize the cost of inventories company can make decisions for ordering, holding, and managing inventories. The purpose of this research is to compare the optimal ordering quantities and total inventory cost between conventional methods and EOQ methods. The research method used is quantitative research with a case study approach through exploration. The variables this research are ordering cost, holding cost, annual demand, and lead time. The analysis techniques used this research are Economic Order Quantity (EOQ), safety stock, and reorder point. Mitra Motor is a business engaged services and sells inventorie, especially Toyota spare parts, Bekasi area. during the store’s operation, the store owner never recorded the quantity of ordered items, resulting a buildup of inventories that caused significant storage costs, especially for fast-moving items such as brake pads and spark plugs. The results of this research show EOQ method can be an alternative for inventory management Mitra Motor. This is evident from the total inventory cost after using the EOQ method calculation for brake pads inventory in 2021 amounting to Rp. 12.474 previously Rp. 48.070, indicating a 27% savings, in 2022 amounting to Rp. 13.096 previously Rp. 49.628, indicating a 26% savings, and in 2023 amounting to Rp. 14.331 previously Rp. 49.821 indicating a 29% savings. As for spark plug inventory in 2021 amounting to Rp. 12.409 previously Rp. 55.500, indicating a 22% savings, in 2022 amounting to Rp. 13.875 previously Rp.57.000, indicating a 24%, and in 2023 amounting to 14.400 previously Rp. 57.114, indicating a 25% savings.